We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
-1
218
2
avatar+1405 

Help Me, pleasesad

 

Multiply: Leave answers with positive exponents.

 

(x)(x-3)

 Feb 5, 2018
edited by ManuelBautista2019  Feb 5, 2018
 #1
avatar+100516 
+2

(x) (x-3)   =

 

(x1) (x-3)

 

Using    (am) (an)  = a(m + n)

 

So  

 

(x1) (x-3)  =  ( x ) (1 - 3)  =  (x)-2  =   1 / x2

 

 

cool cool cool

 Feb 5, 2018
 #2
avatar+1405 
-1

Thank Youlaugh

 Feb 5, 2018

27 Online Users

avatar